Hubungan antara Kebiasaan Belajar dengan Hasil Belajar Matematika pada Siswa Kelas V di SDN Karangrejo 02 Jember - Amrina Rosyada Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Students thought that learning more effective by do assignments and studying when exams only rather than study for daily and long term. Which is study habits consistently needed to improve skills and knowledge. The purpose of the reasearch is to determine whether there is or is not has a relationship between study habits and mathematics learning outcomes. It is a correlational research processed quantitatively analyzed using product moment pearson. The research used 32students and the significance level is 0,05 with 0,349 rtable. The result after calculation rhitung > rtable value are 0,666 > 0,349. The amount of contribution of study habits to learning outcomes is 44%. It can be concluded there is a posiive relationship between study habits and mathematics learning outcomes for grade V students of SDN Karangrejo 02 Jember.
Entry oleh Arif 2026 Februari 06
Keywords: study habits; math learning outcomes